Penetapan Harga Jual Beli Pohon Bonsai Di Desa Curah Kalak Kecamatan Jangkar Kabupaten Situbondo Dalam Perspektif Ekonomi Islam - Huddin, Misba; Febriyanto, Mohammad; Mustofa, Mustofa (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2026)
This article analyzes the determination of buying and selling prices of bonsai trees in Curah Kalak Village, Jangkar District, Situbondo Regency from the perspective of Islamic economics. The study employs a qualitative approach using normative–conceptual analysis supported by empirical data obtained from field observations and documentation. The analysis focuses on the conformity of pricing practices with Islamic economic principles, particularly fairness (‘adl), transparency, mutual consent (taradhi), and benefit (maslahah). The findings reveal that the pricing of bonsai trees is largely influenced by factors such as plant age, aesthetic value, maintenance costs, and market demand. From an Islamic economic perspective, the pricing practices generally reflect acceptable principles, as prices are determined through mutual agreement between sellers and buyers. However, certain practices still require improvement, particularly in ensuring clearer information disclosure to avoid potential uncertainty (gharar). This study contributes to the discourse on Islamic economic practices at the community level and provides practical insights for strengthening sharia-compliant pricing mechanisms in local trade activities.